CULTURAL-MORPHOLOGICAL CHARACTERISTICS OF ISOLATES OF ENDOPHITE BACTERIA ISOLATED FROM MEDICINAL PLANTS: https://doi.org/10.5281/zenodo.15240257 - Tagayeva , L.X.; Normurodova , K.T. (International scientific and practical conference, 2025)
A total of 45 isolates were isolated from the roots, stems, and leaves of medicinal plants found in fields and yards such as Plantago major L., Hypericum perforatum L., Kalanchoe daigremontiana, Cichorium intybus L., Melissa officinalis L., Mentha piperita L., Matricaria recutita L. Among them, it was observed that endophytic bacteria were found relatively more in Kalanchoe daigremontiana and Cichorium intybus L. The KD-L7 isolate from the leaves of the medicinal plant Kalanchoe daigremontiana has a high affinity for 1% casein and 1% starch, and its hydrolysis zone size was found to be 6-10 mm.